P185 META–ANALYSIS OF PLACEBO–CONTROLLED TRIALS OF LEVOSIMENDAN IN ACUTE MYOCARDIAL INFARCTION. (18th May 2022) - Tumminello, G; Cereda, A; Laricchia, A; Carlà, M; Conconi, B; Barbieri, L; Lucreziotti, S; Carugo, S
Abstract: Introduction: Despite the potential beneficial effects in the acute phase of myocardial infarction, the use of Levosimendan in recent guidelines is currently limited to patients with heart failure and a severe reduction in cardiac output not responding to standard therapy. In spite of everything, the haemodynamic effects of the drug that reduces afterload, the beneficial pleiotropic effects on myocardial stunning and the improvement of microcirculatory indices make Levosimendan still an interesting therapeutic prospect in AMI. Purpose of the Study: The study aimed to analyse the available data of the use of Levosimendan in the acute setting of myocardial infarction Materials and Methods This review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) and was conducted and presented according to best practice recommendations, including the Preferred Reporting Items for Systematic Reviews and Meta–Analyses (PRISMA) reporting guidelines. Seven selected studies were included in the meta–analysis. Meta–Analysis Levosimendan treatment was associated with a reduction in one year mortality and adverse event rates, without inconsistency. A trend of the increase of cardiac index and reduction of wedge pressure was evident, with an inconsistent effect on blood pressure and heart rate. No evidence of small study effects was found upon the inspection of funnel plots or regression tests. Finally, possibly given the limited number of included studies, metaregression analysis did not identify any major effect modifier. Discussion: A clearly significant mortality reduction in the acute phase and long–term mortality induced by Levosimendan in AMI is evident. In the acute ischemic field, the haemodynamic properties of Levosimendan may explain part of the benefits. Levosimendan, over an inotropic effect, has a positive effect on ventriculo–arterial coupling, peripheral vasodilation consequently increasing tissue perfusion, anti–stunning effects and anti–inflammatory effects. Conclusions: Our data support the idea that Levosimendan may already have a role in the treatment of acute ischemic heart disease. Further studies, specifically designed to investigate the early role in the treatment of ischemic heart failure are needed.